2000
DOI: 10.1046/j.1365-263x.2000.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of language used by children to describe discomfort during dental pulp‐testing

Abstract: To assess children's experience of pain (1) they need to be presented with a list of words like the ones in this study, (2) the numbers of words chosen by them would represent the severity of pain, and (3) those numbers need to be adjusted for the children's reading comprehension and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
2
12
1
Order By: Relevance
“…Children in these studies have been able to discuss their knowledge and understanding of their condition, the limitations their illness places on their lives, their emotions, and their role in self‐care. Children have also been found to be able to describe their pain experiences; however, the language children used was different to that used by adults. Thus, the overall aim of this study was to give children the opportunity to describe the impact of dental caries on their daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…Children in these studies have been able to discuss their knowledge and understanding of their condition, the limitations their illness places on their lives, their emotions, and their role in self‐care. Children have also been found to be able to describe their pain experiences; however, the language children used was different to that used by adults. Thus, the overall aim of this study was to give children the opportunity to describe the impact of dental caries on their daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…Results from another study have shown that children with good reading comprehension choose fewer words when experiencing discomfort. One possible reason, according to Toole, may be that they are less inclined to choose unfamiliar words [22].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many attempts to develop valid observational measures [11] and means to allow children to report pain [12,13]. However, these have only recently been tested in dentistry for children [14]. Toole et al .…”
Section: Introductionmentioning
confidence: 99%
“…Toole et al . [14] showed that the oldest children gave the greatest estimates, on adjectival measures, of severity of pain during dental pulp testing. On the other hand, when chronological age was controlled statistically, the children with the least well‐developed linguistic comprehension, according to a standard psychometric test, were shown to give the most severe representations of discomfort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation